Hukum Dokter Dalam Pengambilan Keputusan Medis Kritis Pada Pasien - Henri Azis; A. Jaeni; Ateng Karsoma (Journal of Innovative and Creativity, 2025)
Due to clinical complexities in practice, physicians in the Neonatal Intensive Care Unit (NICU), particularly neonatologists, are often confronted with emergency situations that demand rapid and accurate medical decision-making. The Indonesian legal system has not explicitly recognized or regulated protections for the exercise of medical discretion in such emergency conditions. Law No. 17 of 2023 on Health and the Indonesian Penal Code (KUHP), such as Article 359 on negligence causing death, still regulate physicians’ responsibilities under general legal frameworks without considering the specific characteristics of medical emergencies. This creates legal risks for physicians, even when their actions are consistent with clinical procedures and undertaken solely for the patient’s safety. The findings of this research conclude that: (1) The forms of legal accountability for physicians in critical conditions are complex and have not fully reflected substantive justice, comprising four relevant models: first, individual accountability, where physicians are personally liable for the medical actions they take; second, collective accountability, which reflects the reality of medical practice in the NICU; third, fault liability, where physicians can be held accountable if proven negligent; and fourth, strict liability, the most challenging form, where physicians may still be prosecuted even without proof of fault or negligence. (2) Legal protection for physicians performing medical actions as part of professional discretion in neonatal emergencies should take two forms: preventive legal protection, which is proactive in nature, ideally providing physicians with strong and legitimate legal safeguards—such as explicit statutory provisions granting them authority to act in emergencies to save patients without requiring prior written consent from families; and repressive legal protection, which includes legal assistance from professional organizations such as the Indonesian Medical Association (IDI), ethical review by the Indonesian Medical Discipline Honorary Council (MKDKI), or defense through litigation.